Introduction of paediatric laparoscopic cholecystectomy in Scotland: a national review of incidence, outcomes and training implications. Issue 3 (August 2021) - Sekaran, P; Ross, AR; Rooney, A; Duthie, G; Clarke, M; Munro, FD; Sabharwal, AJ
Background: We present a national data series to determine the incidence, outcomes and training opportunities for laparoscopic cholecystectomy among children <16yrs in Scotland as performed by paediatric surgeons. Methods: A retrospective cohort study was performed reviewing laparoscopic cholecystectomy performed at the three children's hospitals in Scotland. Using the National Records Scotland Database mid-year population estimates; age and sex specific annual incidence rates of laparoscopic cholecystectomy were calculated between 1998-2015. Trends in the observed case mix were tested using univariate linear regression and students t-test. Results: Between 1998–2015; 141 paediatric laparoscopic cholecystectomies were performed. The annual rate of cholecystectomy increased from 0.10/100, 000 to 0.88/100, 000 (p = 0.069). Sex specific incidences were identified; 0.00–0.90/100, 000 (p = 0.098) in girls and 0.20–0.86/100, 000 in boys (p = 0.28). Cholecystectomy was more frequent in girls (63%; p = 0.04). No major complications, defined as common bile duct injury or mortality were identified. Overall; 75% of cases were performed by consultants (n = 17 consultants, median = 5 cases, p < 0.05) and 25% by trainees. Conclusion: We have demonstrated that despite a low national case load (8 laparoscopic cholecystectomies per year) paediatric surgeons have been able to perform laparoscopic cholecystectomy safely without major morbidity.